Developing Knowledge, Skills and Attitudes through a Study Group: A Study on Teachers’ Professional Development - Sierra-Piedrahita, Ana María (Íkala, Revista de Lenguaje y Cultura, 2007)
This article presents the results of a qualitative study that explored the development of knowledge, skills and attitudes of a group of foreign language teacher educators and pre-service teachers through their participation in a study group. Sources of data included minutes of meetings, observations, tape recorded meetings, self-assessment forms and interviews. The fi ndings show that teachers developed knowledge about the subject matter and research. Moreover, they developed skills such as research skills, critical thinking and collaborative work, and attitudes such as initiative, commitment, positive attitude towards research, and risk taking. It is concluded that the use of study groups can be an effective strategy for the professional development of teachers. Received: 06-04-07 / Accepted: 06-08-07 How to reference this article: Sierra Piedrahita, A. M. (2007). Developing Knowledge, Skills and Attitudes through a Study Group: A Study on Teachers’ Professional Development. Íkala. 12(1), pp. 279 – 305.